PROSPECTS OF MANUFACTURING TUNNELING AND DRILLING EQUIPMENT TOOLING IN THE RECYCLING OF HIGH-ALLOY STEELS WASTES - D. M. Kukui; F. I. Rudnicki; J. A. Nikolaichik; L. V. Sudnik (Литьë и металлургия)
The technological aspects of processing and remelting of dispersed metal scrap, generated during polishing and grinding of tools made from high speed steel and carbide and lump scrap for the manufacture of drilling equipment and mining equipment are investigated.